Interactive Effect of Capital Structure on Profitability and Earning Per Share of Sharia Bank - M Sandi Marta; Ahmad Gunawan; Syti Sarah Maesaroh; Nugraha Nugraha; Syaiful Bahri (Fakultas Ekonomi dan Bisnis Islam, 2022)
The purpose of this study was to examine the effect of return on assets (ROA) and return on equity (ROE) on earnings per share (EPS) with a debt to equity ratio (DER) as a moderator in Islamic banking in Indonesia. The data was obtained from Islamic banking which was indexed on the Indonesia Stock Exchange from 2016 to 2020. The data was then analyzed using the Moderated regression analysis (MRA) method to determine the relationship and interaction of each variable studied. The results showed that ROA had a positive effect on EPS and ROE had a negative impact on EPS. Meanwhile, DER weakens the relationship between ROA and ROE to EPS. This study confirms that the use of debt has a negative impact on the relationship between ROA and ROE on increasing Islamic banking profits in Indonesia.